IMPLIKASI PENANGANAN MASALAH COMFORT WOMEN TERHADAP HUBUNGAN JEPANG DAN KOREA SELATAN PADA TAHUN 2015-2019 [THE IMPACT OF RESOLVING THE COMFORT WOMEN ISSUE TO JAPAN AND SOUTH KOREA RELATIONS DURING 2015 - 2019] - Jeniffer Gracellia (Universitas Pelita Harapan, 2019)
The issue of comfort women that has occured since 1932 continues to impact bilateral relations between Japan dan South Korea. Various efforts have been made by two countries to deal with this issue, one of which is the agreement in 2015 that stating the comfort women issue has been completed and this agreement cannot be canceled. Instead of solving the problem, this agreement marked as the beginning of a worsening relation between the two countries. Poor relations led to several implications which then became a new problem to Japan and South Korea relations. This research finds that the comfort women issue has given three implications for the relations between Japan and South Korea. First is the Japan-South Korea Trade War in 2019, second is the withdrawal of South Korea from General Security of Military Information Agreement (GSOMIA) and the last is the boycott of Japanese products conducted by South Korean society. The unresolved issue has affected the economy, national security and the social life of the people of both countries.BAHASA INDONESIA ABSTRAK: Permasalahan comfort women yang terjadi sejak tahun 1932 terus memberikan implikasi yang kuat kepada hubungan bilateral antara Jepang dan Korea Selatan. Berbagai usaha telah dilakukan oleh kedua negara untuk menangani permasalahan ini, dimana salah satunya adalah perjanjian pada tahun 2015 yang menyatakan permasalahan comfort women telah selesai dan perjanjian ini tidak dapat dibatalkan. Bukannya menyelesaikan masalah, perjanjian ini menjadi awal dari hubungan kedua negara yang semakin memburuk. Hubungan yang buruk kemudian menimbulkan beberapa implikasi yang menjadi masalah baru di dalam hubungan Jepang dengan Korea Selatan. Berdasarkan hasil penelitian yang telah dilakukan, ditemukan bahwa permasalahan comfort women memberikan tiga implikasi kepada hubungan Jepang dan Korea Selatan yaitu Perang Dagang Jepang-Korea Selatan 2019, penarikan Korea Selatan dari General Security of Military Information Agreement (GSOMIA) dan pemboikotan produk Jepang yang dilakukan oleh masyarakat Korea Selatan. Permasalahan comfort women yang tidak kunjung terselesaikan telah mempengaruhi perekonomian, keamanan nasional, hingga kehidupan sosial masyarakat kedua negara.